Reconfigurable antenna with Kapton for smart wireless communication system - Dahalan, Abdul Halim (2022)
The antenna is a primary part for signal transmission and reception in a telecommunications system. Smart antenna design is a method to enhance the output signal of the normal antenna in order to provide higher level of performance to the consumer. Researchers have developed numerous techniques for smart antennas, including the use of radio frequency switching (RF), Micro Electro Mechanical System (MEMS), algorithms, and Metasurface. Most antennas designed are fixed, and all designs have a limited constraint in terms of creating new frequency, gain and pattern. If this situation occurs, it has the potential to change the purpose of the whole system . The goal of the research is to develop a new Corplanar wave guide (CPW) antenna with a tunable External Parasitic Element (EPE) structure in order to create a heating technique to control the antenna performance. This research examines the use of Kapton material in the design of antenna for telecommunication systems. Kapton is commonly used in the design of radio and microwave frequency antennas. It is flexible material the antenna is made of a Kapton substrate, a patch and copper (FR4) and the dielectric properties of the Kapton substrate vary with temperature. The antenna design in this research used a combination of CPW and Kapton material with direct current (DC) input and peltier device as the heating technique. The temperature difference caused by a voltage change,will have an impact on the dielectrics of the Kapton material, affecting the material’s dielectric state and loss tangent allowing control of the signal frequency, radiation pattern and gain. The X-shape External Parasitic Element (EPE) was able to change to radiation pattern of the antenna at 150o angle and improve the antenna gain from 2 dB to 3 dB. This novel technique differs from the traditional antenna design in that it is less expensive and simpler to implement. The findings of this research result in the development of a new smart antenna design technique that uses a heating concept at the front of the antenna to control the signal frequency, radiation pattern and gain in a telecommunication system.